Perencanaan Pergerakan Menggunakan Game Controller untuk Mengurangi Miskonsepsi pada Kinematika Robot - Mahfud Jiono (Kayon Media, 2021)
An interesting teaching materials that can improve students' understanding in studying theory is very important. Technological developments in the digital era need to be reviewed and can be used as opportunities for the development of interactive teaching materials. With the aim of reducing student misunderstandings in understanding and implementing a concept. For example, the concept of robot kinematics. Kinematics is a control system based on a mathematical approach in converting motor rotation into position and orientation coordinates or instead. In the process of calculation and conversion, students often experience discrepancies between calculations and real implementation. With the existence of teaching materials that are integrated with visual widgets that can represent the robot coordinates of position and orientation, it is hoped that it will reinforce students' understanding. The results of this study indicate that learning with technology integration can help improve understanding between concepts so that they become easier to understand.